(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
CRITICAL ANALYSIS ON LEGAL EDUCATION IN BRAZIL ABSTRACT This article aims to promote a critical analysis of the legal teaching model in force in Brazilian higher education institutions, as well as to verify the role of the teacher in the teaching-learning process. In this sense, part of its historical contextualization in order to delineate the reasons for its poor quality today. It also seeks to situate the law as a cultural object, considering the three dimensions of legal experience: the normative, the factual and the evaluative, so that the legal phenomenon can be fully understood, giving priority to a humanistic formation over the technical-legalistic one. It also emphasizes the importance of the teacher’s role in the teaching-learning process and the need for continuing education focused on pedagogical practice. Finally, it concludes the need for change, presenting some proposals that can contribute to overcoming the crisis experienced. These questions were analyzed using the deductive method, starting from the historical identification about the current legal education model, and then pointing out the current challenges faced by the academic community regarding the quality of education, proposing solutions for this. Keywords: Legal education. Technicality. Criticality.Teaching.